Graphene oxide/acrylonitrile butadiene rubber nanocomposites and their physicochemical properties - Mohammed, Nasser Abd-Ullah (2017)
Studies on the problems pertaining to the rubber industry include looking for ways to address the problem of early deformation mainly due to the weakness in the mechanical and thermal properties of the rubber. Therefore, seeking for alternative fillers (carbonic filler) with desired characteristics such as graphite derivatives is significant for improving the rubber products performance. It is also worth mentioning that in the National Graphene Action Plan 2020, Malaysia plans to invest in graphene for the rubber industry in addition to the other various industrial applications, thus this work is timely. However, there are some challenges related to the homogeneity of the dispersion of graphene derivatives into dry rubber. Therefore, investigating the compatibility of the solvents to reduce agglomeration of fillers in the rubber matrix is important. Also, gaining substantial improvement in the crosslinking density of the rubber structure and thermal stability are strongly desirable to enhance the rubber performance. In this study, graphene oxide (GO) was the candidate filler (prepared by the Hummer's method), exfoliated in aqueous solution. The selected matrix was acrylonitrile butadiene rubber (NBR) which is using for producing various parts in the automobile industry. Acetone was the suitable organic solvent for NBR dissolution and compatible with GO suspension. Unvulcanised GO/NBR nanocomposite was prepared as a first objective to verify the level of distribution GO sheets into NBR. Another aim was to investigate the crosslinking formation before vulcanisation treatment. The results showed that tensile strength was increased to 81.2% compared to the unfilled NBR. The improvement is attributed to the ability of GO networks to restrict the mobility of the NBR molecular chains before vulcanisation treatment. This result could be used effectively in the applications of thermal adhesives. Vulcanised GO/NBR nanocomposite was prepared by combining effective techniques as a new and facile method. The influence of GO on vulcanised GO/NBR nanocomposite properties with different filler contents of GO (0.2 to 2.4 phr - part per hundred rubbers) was investigated as the second objective. The results showed improvement in the mechanical and thermal properties at 1.2 phr of GO compared to unfilled vulcanised NBR. For comparison, a commercial filler of carbon black (CB) reinforced vulcanised NBR was fabricated in order to study the possibility of replacing it with GO/NBR nanocomposite. Graphene nanoplatelets (GNP) were also used to prepare vulcanised GNP/NBR nanocomposite for another comparison of using a different type of graphite derivative. The comparisons as the third objective were performed at 1.2 phr of GO (the percolation threshold) without chemical functionalisation. The morphology analysis, identification of functional groups, and cure characteristics of the different nanocomposites were studied. Based on the filer contents effect, the tensile strength was increased significantly at 1.2 phr in the vulcanised GO/NBR, up to ~149% compared to the unfilled vulcanised NBR. Moreover, based on the filler type, the improvement in GO/NBR nanocomposite was better than those of the vulcanised CB/NBR and GNP/NBR nanocomposites of about 69% and 29.5% respectively. These results were confirmed by the enhancement in the crosslinking density of 38%, 17% and 29% respectively. However, the thermal stability and the glass transition temperatures have the same levels of improvement. Finally, it is concluded that the desired characteristics of GO and the high level of GO dispersion in a polar elastomer such as NBR matrix, have essential roles in the enhancement of the GO/NBR nanocomposite properties.